Innovative development of a spherical parallel robot for upper limb rehabilitation. Issue 4 (2018) - Vaida, Calin; Plitea, Nicolae; Carbone, Giuseppe; Birlescu, Iosif; Ulinici, Ionut; Pisla, Adrian; Pisla, Doina
Post-stroke robotic rehabilitation is an ever increasing field of research that aims to offer custom care with maximised effectiveness. This paper presents the necessity of pursuing further improvements in said field as well as the factors that contributed towards the development of an innovative yet simple spherical-parallel robotic device targeting the rehabilitation of the upper human limb. A conceptual device entitled ASPIRE is proposed. The robotic system kinematics and singularities are derived to assert the robot functionality for the rehabilitation exercises. Moreover, two design structures are presented for the ASPIRE system, and motion simulations are performed.